Половые и фенотипические особенности содержания РНК в гонадах черноморских мидий - Щербань, С.А.; Вялова, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
Data on the total RNA contents of gonads of males and females of mussels Mytilus galloprovincialis at different stages of maturity are presented. Gonads are characterized by various synthesis activities depending on the stage of maturity. The RNA contents increase during maturing, and their values are maximum at the spawning period. No reliable differences between male and female investigated parameters are noted (P > 0.05). Phene groups of mussels with typical colour shell (black, black-brown, brown) and albino-mussels (no pigmentation of shell, mantle, foot) are first investigated. Brown and albino mollusсs have maximum contents of nucleic acids and levels of protein synthesis.